Advances in intelligent long-term vibration-based structural health-monitoring systems for bridges. Issue 7 (May 2022) - Desjardins, Serge; Lau, David
The true realization of the benefits of vibration based structural health monitoring (VBSHM) in real-world applications is acquired through long-term continuous monitoring so that one can attain a detailed grasp of the behavior of the monitored structure. The challenges in long-term continuous VBSHM include: the large volume of accumulated monitoring data; the effective extraction of engineering information amid the influences of noise and uncertainties embedded in the monitoring data; maintaining continuity and consistency in the long-term monitoring data considering that the system and instrumentation may change due to sensor failure or renewal due to advances in sensing technologies. To meet these challenges, this paper presents recent research that has resulted in the development of a framework and specialized signal processing and data analytic tools for long-term continuous VBSHM suitable for real-world monitoring applications of structures in the field. These include efficient tools for large scale intelligent data processing and analysis, management of monitoring database and extracted information relevant to the structural health of the monitored structure. The novel Automated In-Line Full Space Identification (AI-FSI) method is presented to address the needs and challenges associated with long-term continuous VBSHM, such as the automation of all data processing and analysis operations including modal parameter estimations and mode tracking, and the need of minimizing the measurement and computational uncertainties and variability in the operational modal analysis results. A smart self-diagnostic system for the monitoring of the health of the data collection sensors and monitoring system has also been developed that will allow the consistent use of the monitoring data of different sensor configurations and era in the monitoring project. Examples on the efficiency of analyzing the monitoring data collected over 20 years from the Confederation Bridge monitoring project in Atlantic Canada by using the developed novel framework and data analytic tools are presented.